Analisis Transmisi Harga Beras di Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Endang Lastinawati; Andy Mulyana; Imron Zahri; Sriati Sriati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2018)
Lastinawati et al, 2018. Price Transmission Analysis of Rice in Ogan Komering Ilir District, South Sumatra Province. JLSO 7(1):43-49. Price transmission is one indicator of whether or not a marketing system is efficient and also can explain the distribution of welfare between producers and consumers in the marketing channel. This study aimed to analyze the transmission of rice prices which are the basic needs of the Indonesian people, both the price transmission of consumer to farmers, and vice versa, with two groups of rice based on their quality, namely premium and medium rice. This research conducted at Ogan Komering Ilir District, South Sumatra Province. Price transmission was analyzed using price transmission elasticity, using weekly rice price series data from the second week of March 2016 to the second week of September 2018. The results showed that the transmission of consumer prices of premium and medium rice to the price of harvested dry grain at farmer level had an elasticity value not equal to one, and vice versa. This showed that the rice market in Ogan Komering Ilir Regency was in elastic and less efficient, because prices were transmitted asymmetrically.